2021
DOI: 10.3390/antibiotics10080925
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Circular Bacteriocin AS-48 against Clinical Multidrug-Resistant Staphylococcus aureus

Abstract: The treatment and hospital-spread-control of methicillin-resistant Staphylococcus aureus (MRSA) is an important challenge since these bacteria are involved in a considerable number of nosocomial infections that are difficult to treat and produce prolonged hospitalization, thus also increasing the risk of death. In fact, MRSA strains are frequently resistant to all β-lactam antibiotics, and co-resistances with other drugs such as macrolides, aminoglycosides, and lincosamides are usually reported, limiting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…All strains of S. aureus included in this study were observed to be either moderate or strong biofilm formers. This assumes significance as these strains were isolated from clinical cases and clinical isolates have been demonstrated to form robust biofilms impacting adhesion and pathogenesis (20). The antibiofilm activity of klebocin against mature biofilm of S. aureus observed in this study is in accordance with an earlier study by Okuda et al, (21) who studied the effect of bacteriocins on MRSA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All strains of S. aureus included in this study were observed to be either moderate or strong biofilm formers. This assumes significance as these strains were isolated from clinical cases and clinical isolates have been demonstrated to form robust biofilms impacting adhesion and pathogenesis (20). The antibiofilm activity of klebocin against mature biofilm of S. aureus observed in this study is in accordance with an earlier study by Okuda et al, (21) who studied the effect of bacteriocins on MRSA.…”
Section: Discussionsupporting
confidence: 90%
“…Our studies with klebocin on pathogenic S. aureus MRSA strains isolated from clinical samples showed that klebocin was effective in inhibiting the growth and bio-film formation by this pathogen. MRSA isolates have been shown to develop biofilms (19,20) formation which is an important aspect of many Staphylococcus aureus infections. Further, biofilm formation by strains could be weak, moderate or strong (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bacterial lysis induced by AS-48 is not the only ultimate cell-death mechanism since in many cases no bacteriolysis has been observed (for instance, members of the Phylum Actinomycetota such as Micrococcus, Mycobacterium, Nocardia, Cutibacterium, Gardnerella, or the majority of the susceptible Gram-negative bacteria such as Agrobacterium tumefaciens, Salmonella spp., or Escherichia coli). Recently electronic scanning microscopy images of AS-48-treated Staphylococcus aureus showed that the cells remain together after the division septa formation, which suggests alternative unraveled mechanisms of action rather than solely membrane lysis (Velázquez-Suárez et al, 2021).…”
Section: As-48 Mechanism Of Action: Minimizing Resistance Developmentmentioning
confidence: 99%
“…Still focusing on bacteriocins, Velázquez-Suárez and collaborators [ 9 ] investigate the antimicrobial activity of the circular bacteriocin AS-48 against Staphylococcus aureus , a clinical multidrug-resistant bacterium that can cause various problems, ranging from simple infections to severe sepsis and death. They isolate multiple S. aureus strains from different health care units at the University Hospital of Granada in Spain, and investigate the antimicrobial-resistance profile of those isolates, identifying several that are multi-resistant to various antibiotics, more commonly the ones isolated in the ICU and Respiratory and General Pathology services.…”
mentioning
confidence: 99%